Censorium cinema and the open edge of mass publicity - Mazzarella, William 1969- (Duke University Press, 2013)
Performative dispensations : the elementary forms of mass publicity -- Who the hell do the censors think they are? Grounds of the censor's judgment -- We are the law! Censorship takes to the streets -- Quotidian eruptions : aesthetic distinction and the extimate squirm -- Obscene tendencies : censorship and the public punctum
Includes bibliographical references and index. - Description based on print version record
Keywords: Geschichte; Motion pictures / Censorship / History / India; Motion pictures / History / 20th century / India; Motion pictures / Social aspects / India; Motion pictures / Political aspects / India; Filmzensur; Indien